Pengembangan Media Pembelajaran Digital pada Materi Gaya Berbasis Web untuk Meningkatkan Prestasi Belajar IPAS Peserta Didik Kelas IV Sekolah Dasar - Ni Putu Liana Octavyanti; Dewa Bagus Sanjaya; I Made Candiasa (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The low learning achievement of students occurs due to the lack of availability of learning support media that can be fun and increase students' enthusiasm to improve their abilities. The purpose of the following research is to create a web-based digital learning media that meets the validity, practicality, and effectiveness in order to improve the learning achievement of social studies students in grade IV of elementary school. ADDIE (Analysis, Design, Development, Implementation, and Evaluation) is the development model used in this study. The Learning Object Review Instrument (LORI) is used to test the validity of media and content. In addition, the User Experience Questionnaire (UEQ) tool was used to carry out a practicality test. Effectiveness was analyzed with a single-tail t-test. This research produces digital learning media in the form of links that contain various resources, such as games, learning films, and assessment questions, in a web-based format. The average value for the value of material validity and media validity is 4.6 with a very valid category. The practicality of web-based digital learning media received a very practical qualification with teachers getting an average score of 2.80, while students got an average score of 2.29. The impact of the implementation of web-based digital learning media is effective in increasing the science learning achievement of grade IV elementary school students, as evidenced by the calculation of 76,636, which is higher than the table of 2,051 in the effectiveness test. Based on the following findings, it can be said that the digital learning media on web-based style materials developed is valid, practical, and effective to improve the learning achievement of science science students in grade IV elementary school.